Frequency of Autoimmune Hemolytic Anemia in Chronic Lymphocytic Leukemia - Malik, Saira Nasr (International Journal of Pathology, 2021)
Introduction: Patients suffering from chronic lymphocytic leukemia (CLL) develop autoimmune complications between 5–10%, which primarily cause cytopenias. These autoimmune cytopenias can occur at various stages of CLL and do not have independent prognostic significance.Objective: To determine the frequency of autoimmune hemolytic anemia in patients having chronic lymphocytic leukemiaSetting: Department of Hematology, Hayatabad Medical Complex, Peshawar.Study Design: Descriptive Cross sectional studyDuration: 6 monthsMaterial & Method: In this study, 253 patients were investigated and observed. Blood counts were performed on automated hematology analyser. Examination of Bone marrow included both bone marrow aspiration as well as trephine biopsy. Both peripheral blood smears as well as bone marrow smears was stained with Geimsa. Haematoxylin and eosin stains were used for trephine biopsies. Coomb’s test was performed on blood samples of CLL patientsResults: Mean age was 58 years in this study with SD ± 11.341. Male patients were 72% and 28% patients were female. The frequency of autoimmune hemolytic anemia was found to be 8%only.Conclusion: Our study concludes that the frequency of autoimmune hemolytic anemia was 8% in patients suffering from chronic lymphocytic leukemia